ASPHALT-RESIN-WAX DEPOSITS ANALYSIS WITH PETROLEUM REFINERY EQUIPMENT USAGE - Bondar, Nadejda; Denysyuk, Anatoliy; Simonov, Yuriy; Tertyshna, Olena; Snizhko, Lyubov (Proceedings of National Aviation University (archive), 2014)
The methodology and analysis of wax deposits formed in-water-cooling tower, cistern and tank from wax petroleum were developed. It was shown, that deposits consist of organic (>90%) and inorganic components – the first one was enriched by high molecular wax hydrocarbons, the second one – by mechanical impurities. The methods of deposits utilization were proposed